The use of carbon and nitrogen stable isotopes for the detection of poultry offal meal in meat-type quail feeds - Sernagiotto, E R; Ducatti, Carlos [UNESP]; Sartori, José Roberto [UNESP]; Stradiotti, A C; Maruno, M K; Araujo, P C; Carvalho, F B; Pezzato, Antonio Celso [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The objective of the present study was to trace the inclusion of poultry offal meal (POM) in the diet of meat-type quails reared for a long period using the technique of stable isotopes. A number of 320 quails were randomly distributed into eight treatments: vegetable diet (T1), and a diet containing 8% POM were fed until the end of the experimental period (T2) or replaced by the vegetable diet on day 42 (T3), 56 (T4), 70 (T5), 84 (T6), 98 (T7), and 112 (T8). Breast muscle samples were collected from four birds randomly selected per treatment every 14 days. The obtained isotope results were submitted to multivariate analysis of variance (MANOVA) with the aid of the GLM procedure of statistical SAS program. Treatments were different from T1 when birds were sacrificed at least two weeks after the diet was changed. T2 results were different from T1 in all evaluated periods. It was concluded that it is possible to trace poultry offal meal inclusion in a strictly vegetable diet after the diet was changed for at least 14 days.
Keywords: Carbon-13; quail production; stable isotopes; nitrogen-15; traceability